A A Study on fly ash Geopolymer Modified Asphalt Binder - SETH, ZULKEFLI; AMAN, MOHAMAD YUSRI (Recent Trends in Civil Engineering and Built Environment, 2022)
Asphalt has widely been used as road pavement all over the world. But the most crucial part was, asphalt pavement must be able to withstand various of problem. Realizing these facts, asphalt modified must be evaluated to achieve certain types of improvement. The objective of this research is to conduct a comparative study of the physical properties of different asphalt binder penetration prepared with various fly ash geopolymer content. This study focuses on the strength and hardness of asphalt binder with modified by fly ash geopolymer. In this study, asphalt binder grade penetration 60/70 and 80/100 with 0%,3%, 5%, 7%, 9%, 11% fly ash geopolymer by mass of asphalt binder. The physical test of asphalt binder such as, penetration test, softening point test, ductility test and rotational viscosity test was conducted. The best strength and hardness of asphalt binder modified by fly ash geopolymer was 60/70 grade penetration with 9% fly ash geopolymer. This can be shown by lesser penetration and ductility result, while higher softening point timer and rotational viscosity test result.